Distribution and risk assessment of radionuclides released by Fukushima nuclear accident at the northwest Pacific. (April 2015) - Yu, Wen; He, Jianhua; Lin, Wuhui; Li, Yiliang; Men, Wu; Wang, Fenfen; Huang, Jiang
Abstract: In order to understand the impact of Fukushima Nuclear Accident (FNA) on the marine environment, seawater and a composite squid ( Ommastrephe bartrami ) sample were collected on the monitoring cruise XT01 during June 16–July 4, 2011. The concentration levels of Cesium-134, Cesium-137, Strontium-90, Silver-110m, Cobalt-58 and Cobalt-60 were measured both for the seawater and squid samples. The elevated activity levels of Cesium-134 and Cesium-137 were found in the sampling area. Cesium-134 and Silver-110m, which were usually undetectable before FNA, were also found in the squid sample, with the activity levels of 1.65 ± 0.13 Bq/kg-wet and 0.07 ± 0.01 Bq/kg-wet, respectively. The radiological assessment result showed that the radioactive release from the FNA would not have a significant adverse effect on marine biota at the population level. Highlights: Field marine radioactivity monitoring were conducted in 4 months after FNA. Elevated activity levels of Cs-137, Cs-134 and Sr-90 in seawater were found. Cs-134 and Ag-110 m were found in the squid sample. Radiological risk assessment on marine biota was done.